Use of a proton pump inhibitor: Not more not less - Tekin, Fatih (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Tekin F. Use of a proton pump inhibitor: Not more not less. Turk J Gastroenterol 2019; 30(6): 504.